Ultrastructure of the Cell Wall of Bacillus polymyxa - Nermut, M. V. (1967)
The macromolecular arrangement on the surface of Bacillus polymyxa was revealed by metal shadowing of whole cells and wall fragments; it consisted of a rectangular array of 70-A globules with a repeating interval of 100 A. The substructure was studied in plan with phosphotungstic acid (pH 6) or uranyl acetate as negative stains of fragments and was studied also in profile with sections of embedded material. Staining of sections of cells fixed with glutaraldehyde showed that layering (approx. 80-A dense, 40-A light, and 120-A dense layers, outermost layer first) could be demonstrated in the cell wall with lead or uranyl acetate, used together or separately. The outer “dense” layer corresponded to the regularly arrayed structure (RS); it was removed by guanidine hydrochloride, sodium lauryl sulfate, cold formamide, and by trypsin. The RS layer (isolated by a hydrogen bond breaking reagent, guanidine hydrochloride) was disrupted by agents such as sodium lauryl sulfate or damaged by 3 m sodium chloride. Qualitative chemical tests, ultraviolet absorption, and removal by trypsin indicated that the structured layer consisted mainly of protein, but exact characterization was not attempted. The globular units making up the layer consisted of a small number of subunits, imperfectly resolved by negative staining. The underlying polysaccharide appeared to be covalently bound to the deepest (probably mucopeptide) layer since it required “hot” formamide for its removal. A survey of species was not made.